PENINGKATAN PRODUKSI TANAMAN PANGAN DENGAN MELIBATKAN P4S DI PROVINSI SULAWESI SELATAN - Budi Darma Putra; Muhammad Sidiq (Jurnal Eboni, 2022)
The agricultural sector is important because it is a crucial food security sector during an economic crisis. It is hoped that through the Increase in Food Crop Production activities in South Sulawesi, it will be able to increase the knowledge and insight of participants through the process of providing material from the facilitator. The implementation of technical guidance is carried out in 8 (eight) districts in South Sulawesi using different materials because they adjust to the potential that exists in each area. Paddy technical guidance activities were carried out in four districts of South Sulawesi Province, P4S locations, which are food crop-producing areas, especially rice, with a total of 200 (two hundred) participants, consisting of farmers, millennial farmers, farmer groups, farmer women's groups, and P4S managers, while mentoring corn technical implementation was carried out at the P4S location in Maros, Takalar, Gowa, and Bantaeng Regencies, which are food crop-producing areas, especially corn, with a total of 200 (two hundred) participants, consisting of farmers, millennial farmers, farmer groups, women farmer groups, and P4S managers. From the results of the evaluation of the implementation of activities, there was an increase in knowledge of the material provided in rice technical guidance activities with an average value of 39.68 while in corn technical guidance activities there was an increase in knowledge with an average value of 31.65